Diversity, functional traits and assembly processes of diatom community in the aquatic-terrestrial ecotone: a case study of Danjiangkou Reservoir, China - Lyu, Xucong; Chen, Haiyan; Jin, Jialin; Yuan, Huatao; Dong, Jing; Gao, Yunni; Gao, Xiaofei; Zhang, Jingxiao; Li, Xuejun (Frontiers in Microbiology, 2025)
Soil diatoms are essential components of microalgae communities in aquatic-terrestrial ecotones, contributing to primary production, organic matter production, nutrient cycling, and ecosystem stability. However, the functional traits and community assembly processes of diatoms in these ecotones remain poorly understood. This study used 18S rDNA high-throughput sequencing and functional trait analysis to investigate the dynamics, driving factors, and assembly processes of diatom communities in the aquatic-terrestrial ecotone of the Danjiangkou Reservoir. Significant differences in diatom diversity and composition were observed between waterward (frequently submerged) and landward zones (exposed to alternating wet and dry conditions). Functional traits revealed that larger, highly motile species dominated waterward communities, while smaller, less motile taxa were prevalent in landward zones. Total phosphorus (TP), soil organic matter (SOM), and magnesium (Mg2+) were key environmental drivers of taxonomic and functional traits. Community assembly in both zones was primarily driven by random processes; however, deterministic processes, particularly heterogeneous selection, had a stronger influence in the landward zone, reflecting significant environmental filtering. These findings enhance understanding of biodiversity and community assembly in aquatic-terrestrial ecotones and provide valuable insights into their ecological dynamics.